2015
DOI: 10.11646/phytotaxa.202.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Resolving Tiarosporella spp. allied to Botryosphaeriaceae and Phacidiaceae

Abstract: The type species of the genus Tiarosporella, T. paludosa, is epitypified and confirmed as a member of the Botryosphaeriaceae. Based on morphology and DNA sequence data of the large subunit nuclear ribosomal RNA gene (LSU, 28S) and the internal transcribed spacers (ITS) and 5.8S rRNA gene of the nrDNA operon, the genus Tiarosporella is shown to be poly-and paraphyletic. A group of isolates morphologically similar to T. paludosa cluster to the Phacidiaceae (Phacidiales, Leotiomycetes) and we accommodated them in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Crous Crous et al (2015b) introduced this genus and showed it belongs to Botryosphaeriaceae. Li et al (2016a) Foliophoma Crous Crous & Groenewald (2017) introduced this coelomycetous genus.…”
Section: Catenulomyces Egidi and De Hoogmentioning
confidence: 99%
See 2 more Smart Citations
“…Crous Crous et al (2015b) introduced this genus and showed it belongs to Botryosphaeriaceae. Li et al (2016a) Foliophoma Crous Crous & Groenewald (2017) introduced this coelomycetous genus.…”
Section: Catenulomyces Egidi and De Hoogmentioning
confidence: 99%
“…Mucoharknessia Crous et al Crous et al (2015b) introduced this genus and showed it belongs in Botryosphaeriaceae in their phylogenetic analyses. This placement was confirmed by Wijayawardene et al (2016).…”
Section: Catenulomyces Egidi and De Hoogmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this single locus, WGD fungi resolve closely with E. urbisrosarum, E. tritici, T. madreeya. The genus of Tiarosporella was recently resolved into four genera (Tiarosporella, Marasasiomyces, Eutiarosporella, and Mucoharknessia) (Crous et al 2015). Accordingly, a subsequent tree was performed comparing the ITS sequences (369 bp) from these new genera (and species) with all of the WGD isolates ( Supplementary Fig.…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
“…This has lead to a significant refinement in the resolution of these genera Slippers et al 2013). Previously, genera that were poorly resolved, such as the genus of Tiarosporella (now Tiarosporella and Eutiarosporella (Crous et al 2015)), have now been characterised and their genetic relationship to other Botryosphaeriaceae described Slippers et al 2013;Crous et al 2006Crous et al , 2015.…”
Section: Introductionmentioning
confidence: 99%